The Determinants of Maqasid Shariah Based Performance of Islamic Banks in Indonesia - Siti Amaroh; Masturin Masturin (Ekonomi Syariah IAIN Kudus, 2018)
This study aims to examine the determinants of maqasid shariah based performance of Islamic banks in Indonesia. The data was extracted from the published annual audited reports of Islamic banks in Indonesia during the period 2014-2017. This research used correlation and multiple linear regression analysis to examine the proposed hypotheses. Maqasid shariah based performance was proxied by maqasid index. The proposed factors as determinants of maqasid shariah based performance are profit loss sharing financing, cost efficiency, and risk taking behavior. The results of this research revealed that profit sharing financing positively influences maqasid shariah based performance, but risk taking behavior has a negative impact. Cost efficiency does not influence maqasid shariah based performance. The implication of this finding is that Islamic banks should have commitment to realize maqasid shariah through increasing their profit loss sharing financing in the mudharabah and musharakah modes